"A Painful Homecoming": Harry Potter Fanfiction and Nostalgia via All the Young Dudes by MsKingBean89 - Heise, Nina (2024)
In this paper, I will consider fanfiction as an inherently nostalgic group of texts, an argument that has not yet been explored in much detail within fan studies. A close reading of one of the most popular Harry Potter fanfictions, MsKingBean89’s All the Young Dudes, will serve to demonstrate this point. My analysis will situate the text in the context of Britain’s vote to leave the EU and the vote’s aftermath. In this moment of crisis, All the Young Dudes demonstrates a nostalgic longing for community and a habitable national identity, partially evoking conservative ideas of British cultural hegemony despite politically progressive gestures in both the text and paratext. Through my analysis, I aim to show how fanfiction can be read not only as an affective adaptation of a source text but also as political commentary on the moment of its publication.